(untitled) (Indian Journal of Arid Horticulture, 2017)
An experiment was conducted on 6 year-old- plants of karonda at the Horticultural Research Station of Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal to know the effect of different growth regulators on fruit yield and physico-chemical composition of fruits. There were five treatments viz., NAA at 20, 40 ppm; GA at 20 and 40 ppm and control (water spray) which were sprayed two times i.e., at 50% flowering stage and 21 days after 1st spray. The experiment was conducted following the randomized block design having four replications. The study clearly indicated that plant growth regulators were effective at different concentration in increasing fruit yield and physico-chemical characteristics of fruits. Application of NAA at 20 ppm resulted in maximum fruit set (93.62% ), fruit retention (83.0%) and fruit yield ( 4.07 kg/plant). The treatment also increased fruit weight and pulp content while GA at 20 ppm was found to be the best for increasing TSS (8.87°B), total sugars (6.05%), ascorbic acid (34.00 mg/100 g) and anthocyanin (3.87 mg/100 g pulp) contents followed by NAA 20 ppm. Considering the over all performance and lower market price, the NAA at 20 ppm is recommended for higher production of quality karonda fruits in new alluvial zone of West Bengal.